Developmental biology - Gilbert, Scott F. (Sinauer Associates, 2003)
"Developmental Biology", seventh edition and on contemporary developmental biology is written primarily for second and final year undergraduate students of biology but will also be useful for introducing graduate students and medical students to developmental biology. In addition to exploring and synthesizing the organismal, cellular and molecular aspects of animal development, the seventh edition expands its coverage of the medical, environmental, and evolutionary aspects of developmental biology.